Zebra Swallowtail Protographium marcellus (Cramer) (Insecta: Lepidoptera: Papilionidae) - Donald W. Hall; Jerry F. Butler (EDIS)
Also published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/bfly/zebra_swallowtail.htm